If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(4 + 5) = 2x Combine like terms: 4 + 5 = 9 2x(9) = 2x Reorder the terms for easier multiplication: 2 * 9x = 2x Multiply 2 * 9 18x = 2x Solving 18x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 18x + -2x = 2x + -2x Combine like terms: 18x + -2x = 16x 16x = 2x + -2x Combine like terms: 2x + -2x = 0 16x = 0 Divide each side by '16'. x = 0 Simplifying x = 0
| 7+8(-8r-5)= | | x-2/2x^3-3x^2-mx-6 | | 3x-1=4/5 | | 9b-5=3b-.8 | | 48x+56=144x+48 | | 4+6g=4(g+4) | | 2x+30+y-12=180 | | 97+x+27+64=180 | | 97+x-64+27=180 | | .5(6x-8)=3x+6 | | 2x^2+7t+9=0 | | 94+x+64+27=180 | | 4/7=y-2/3= | | 4(4w+2)=-3 | | 0=4x+2y-18 | | -6(2t+9)=-126 | | 3*x+1=63 | | 6(3d+5)=75*d | | 21+4c=47 | | 2y+7x=-9 | | -y+148+18=180 | | 10(s-8)=-139 | | k/2-10=7 | | 2tsquared+7t+9=0 | | (X+3)*4=(x-9)*(-2) | | 5x+148+18=180 | | 12z-4=26 | | 4(x-3)=3(1+x) | | f(x)=5x^3+6x^2+x | | 12.4y+14=6y-2*y | | 3/p-2=-29 | | 4n+6-(5n+3)=0 |